2014
DOI: 10.1017/s175577391400023x
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the selection bias in roll call votes: party group cohesion in the European Parliament

Abstract: Legislative politics scholars rely heavily on roll call vote (RCV) data. However, it has been claimed that strategic motives behind RCV requests lead to overestimating party group cohesion and, thus, biased findings on legislative behaviour. To explore this claim, we distinguish between two types of bias, a 'behavioural bias' and a 'selection bias'. A recent rule change in the European Parliament, making RCVs mandatory on all final legislative votes, presents the unique opportunity to evaluate the latter. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…Stated differently, contention in committee is a poor predictor of RCV requests. While previous studies (Finke, 2015;Yordanova and Mu¨hlbo¨ck, 2014) have suggested that RCV requests are biased towards contentious issues in plenary, this does not seem to be the case with committee decisions. This finding suggests that the nexus between decision-making in committee and voting in plenary may be imperfect (Yordanova, 2011: 609).…”
Section: Discussion and Outlookmentioning
confidence: 75%
See 2 more Smart Citations
“…Stated differently, contention in committee is a poor predictor of RCV requests. While previous studies (Finke, 2015;Yordanova and Mu¨hlbo¨ck, 2014) have suggested that RCV requests are biased towards contentious issues in plenary, this does not seem to be the case with committee decisions. This finding suggests that the nexus between decision-making in committee and voting in plenary may be imperfect (Yordanova, 2011: 609).…”
Section: Discussion and Outlookmentioning
confidence: 75%
“…Indeed, there have been some notable interventions to the debate which have capitalized on this procedural reform to trace the selection mechanism (Hug, 2016;Yordanova and Mu¨hlbo¨ck, 2014). Therefore, one might argue that part of the theoretical puzzle of what is driving RCV requests is solved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Note that in the EP, not all votes are taken by roll call, which may lead to a selection effect. See Yordanova and Mühlböck () for a discussion and overview of the literature.…”
mentioning
confidence: 99%
“…Using the new rule on mandatory RCVs on final acts as intervention, Yordanova and Mühlböck (2015) showed that the cohesion of political groups is higher on all votes than was previously estimated based on requested RCVs. They argue that this shows that going on record was mostly requested on contentious issues.…”
mentioning
confidence: 75%